Marketing no MMA: a identificação dos atributos do esporte para captação de patrocínio e as possíveis associações com potenciais marcas patrocinadoras - Siani, Sergio Ricardo (2017)
The fight sport known as MMA – Mixed Martial Arts, which in Portuguese corresponds to Artes Marciais Mistas, has lived in the last decade a very successful trajectory of increase and sustained, since the beginning, a singular relationship with Brazil – country that originated in the 20th century a kind of fight known as “Vale Tudo”, “Anything goes”, in English – being such modality the start of what is worldwide conceived as MMA. In the field of marketing management, the interest of sports marketing on such modality of sport is focused not only in the aspects provided by events related to that, but mainly in the increase potential of its globalized market. Defining a marketing strategy for such modality is still a challenge, since not all brands are willing to sponsor a fight event. The present study, which aims to investigate with attributes of MMA sport can establish a synergy with potential brands of interest of event organizers, with the intent to contribute to the theory of sports marketing and also contribute to the MMA event’s organizers may have sponsorship for their events, is not an easy task, because apart from being a good product to offer (event, athlete, location and so on) the promotor company “must define its own action strategy”. In both qualitative and quantitative nature, this research was carried out in three different phases: first, it was searched among MMA event’s organizers, by semi-structured interviews, to understand which brands or sponsors would be present in the dreamed events. The second phase, with was quantitative, applied a survey questionnaire, along with the audience of three MMA events and the motives behind the intention to watch such events. The results obtained in the first phase of the study, that is, the identification of the favorite brands of the event’s organizers were: Nike, Coke, Reebok, Banco do Brasil and Honda; the data obtained in the second phase consisted of getting the MMA attributes which were: adrenaline, emotion, joy, pleasure and aggressiveness, propelled the third and last phase of this study, in which, again, by the application of survey questionnaires, there were associations between brands and attributes. After carrying out four statistical tests, this researchwork reaches the conclusion that the atribute most linked to MMA was adrenaline and as for brand Nike was chosen. The aggressiveness was pointed out as a kind of attribute in which the audience related to this kind of sport, what generated the hypothesis of considering such modality as an aggressive one both in a view that only people who had never had any connection with MMA at all